2011
DOI: 10.1111/j.1365-2141.2011.08913.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of antibody response to immunization in paediatric survivors after allogeneic haematopoietic stem cell transplantation

Abstract: Summary The long-term antibody responses to re-immunization in recipients of allogeneic haematopoietic stem cell transplantation (allo-HSCT) have not been well studied. We prospectively and longitudinally evaluated the antibody responses to 8 vaccine antigens (diphtheria, tetanus, pertussis, measles, mumps, rubella, hepatitis B, and poliovirus) and assessed the factors associated with negative titres in 210 allo-HSCT recipients at St. Jude Children’s Research Hospital. Antibody responses lasting for more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 39 publications
4
38
1
2
Order By: Relevance
“…Inaba et al 15 demonstrated that 490% of the studied HSCT patients were able to maintain long-term protective Ab levels for tetanus, rubella, poliovirus and diphtheria. In contrast, the longterm response rates to pertussis, measles, mumps and hepatitis B were only 25, 66.7, 61.5 and 72.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inaba et al 15 demonstrated that 490% of the studied HSCT patients were able to maintain long-term protective Ab levels for tetanus, rubella, poliovirus and diphtheria. In contrast, the longterm response rates to pertussis, measles, mumps and hepatitis B were only 25, 66.7, 61.5 and 72.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the longterm response rates to pertussis, measles, mumps and hepatitis B were only 25, 66.7, 61.5 and 72.9%, respectively. 15 The seroconversion rates for the live-attenuated JE vaccine (SA 14-14-2) in healthy children were 95% for both the single-dose and 2-dose Abbreviations: HSCT = hematopoietic stem cell transplantation; JE = Japanese encephalitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Immunity to measles, mumps and rubella has been shown to wane continuously following HCT and leaves the majority of patients susceptible to infection within 5 years of their transplant. [4][5][6][7][8][9] Table 1 summarizes the peer-reviewed studies published to date on the use of the trivalent measles, mumps and rubella Live vaccines post HCT CJ Forlenza and TN Small vaccine following autologous and allogeneic HCT, [4][5][6][7][8][9][21][22][23][24] including the pro and cons of each study. To date, there have been no reports of severe adverse reactions following MMR.…”
Section: Measles Mumps and Rubellamentioning
confidence: 99%
“…Response to mumps was observed in 460% of patients and against rubella in 475%. [4][5][6][7][8][9][21][22][23][24] Two studies have demonstrated that MMR can be safely and effectively administered o2 years post HCT, particularly if the patient has no evidence of active chronic GVHD, is off immunosuppressive therapy and is at least 15 months post HCT. 13,14,22 There is limited data on MMR response in recipients of an unrelated, HLA-mismatched-related or cord blood transplant.…”
Section: Measles Mumps and Rubellamentioning
confidence: 99%